Shadows of the past: Temporal retrieval effects in recognition memory - Schwartz, Greg (2005)
We examine whether temporally defined associations play a role in item recognition. The role of these associations in recall tasks is well-known; we demonstrate an important role in item recognition as well. We find that subjects are significantly more likely to recognize a test item as having been previously experienced if the preceding test item was studied in a temporally proximal list position. Further analyses show that this associative effect is almost entirely due to the highest confidence recognition judgments.